CSR PT. Kaltim Prima Coal: Nyata atau Tidak? - Puspitasari, Ayu (APSSAI ACCOUNTING REVIEW, 2023)
The purpose of this research is to comprehend and analyze the semiotic and rhetorical aspects of disclosure in PT. Kaltim Prima Coal's Corporate Social Responsibility Report. This study is descriptive qualitative and employs the content analysis method. The findings of the study show that KPC has implemented CSR and has paid close attention to social and environmental issues. This is done with the goal of establishing a positive corporate image. The research findings have been supported by triangulation of data sources through news coverage in the mass media demonstrating various CSR activities carried out by KPC, ensuring that the rhetoric on KPC's CSR disclosure is appropriate.